AM Associations of Bamboo Rhizosphere in Different Study Sites of Tamil Nadu - Ravikumar, R.; Ananthakrishnan, G.; Girija, S.; Ganapathi, A. (Indian Forester, 2001)
In the present study, natural Bamboo growing areas in Tamil Nadu were surveyed to confirm AM fungal associations and it reveals that AM fungal has intimate association with Bamboo in natural habitat. Nineteen species of AM fungal spores have been identified from Bamboo rhizosphere in five districts of Tamil Nadu. Among the AM fungal species Glomus fasciculatum was dominant.